2021
DOI: 10.15585/mmwr.mm7015e3
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits for COVID-19 by Race and Ethnicity — 13 States, October–December 2020

Abstract: Hispanic or Latino (Hispanic), non-Hispanic Black or African American (Black), and non-Hispanic American Indian or Alaska Native (AI/AN) persons have experienced disproportionately higher rates of hospitalization and death attributable to COVID-19 than have non-Hispanic White (White) persons (1-4). Emergency care data offer insight into COVID-19 incidence; however, differences in use of emergency department (ED) services for COVID-19 by racial and ethnic groups are not well understood. These data, most of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 4 publications
2
35
0
Order By: Relevance
“…The effects of ethnicity on SARS-CoV-2 infection and disease severity remain largely unknown [ 8 ]. Data reported by the Centre for Disease Control (CDC) suggest that COVID-19 disproportionally affects certain ethnicities [ 37 ]. However, due to other cofounding factors, such as socioeconomic factors and variable access to healthcare, it is challenging to determine whether there is an underlying mechanism to explain the observed disparities in the humoral response between different ethnic groups [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of ethnicity on SARS-CoV-2 infection and disease severity remain largely unknown [ 8 ]. Data reported by the Centre for Disease Control (CDC) suggest that COVID-19 disproportionally affects certain ethnicities [ 37 ]. However, due to other cofounding factors, such as socioeconomic factors and variable access to healthcare, it is challenging to determine whether there is an underlying mechanism to explain the observed disparities in the humoral response between different ethnic groups [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are primarily two approaches to taking social media data, as psychological data and coding them into psychological variables. One such approach is machine learning, which includes methods such as regression and Latent Dirichlet Allocation ( Schwartz et al, 2013 ; Park et al, 2015 ), support vector machine ( Hutto and Gilbert, 2015 ), long short-term memory, convolutional neural network ( Wang et al, 2017 ; Husseini Orabi et al, 2018 ), cross autoencoder ( Lin et al, 2014 ), and the more recently introduced transformer-based pre-trained language models ( Zhang et al, 2020 ). The other is rule-based modeling, which includes the widely used Linguistic Inquiry Word Count (LIWC) and the sentiment analysis tool VADER (i.e., Valence Aware Dictionary and sEntiment Reasoner).…”
Section: Machine Learning Methods In Capturing Psychological Conceptsmentioning
confidence: 99%
“…For example, a CDC official report suggested that the impact of COVID-19 on people is different by race (Smith et al, 2021). Specifically, Hispanic, Black, and Indian Americans have more disproportionate COVID-19 incidents, hospitalization, and mortality than White people (Smith et al, 2021). Moreover, socioeconomic status also influences the impact of COVID-19 such that the poor are likely to experience more difficulties during COVID-19 (Raut et al, 2020).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although race and ethnicity are not the only measures for assessing health disparities, these measures have been integral to CDC’s understanding of the health outcomes associated with COVID-19 ( 8 10 ). This analysis demonstrates that alternative methods for analyzing race and ethnicity data when data are incomplete can lead to different interpretations about disparities and highlights the importance of working with experts to identify methods for analyzing and tracking disparities when race and ethnicity data are incomplete.…”
Section: Discussionmentioning
confidence: 99%